'Everyone knew everyone's business': Being a parent with housing issues in rural areas. (December 2016) - Reupert, Andrea; Jones, Rebecca; Sutton, Keith; Maybery, Darryl
This research explored the intersection between participants' parenting role and housing difficulties, in rural communities. Thirteen parents were recruited from drug and alcohol and mental health agencies in rural Australia. Transcripts were analysed using content analysis, along with inter-rater reliability. The quandary of gaining access to their children while living in inadequate housing was indicated. Participants also described the 'spiral' nature of problems, highlighting the interrelated nature of mental illness, substance use, housing difficulties and losing access to children. The impacts of housing problems on parenting roles and children were described as well as those supports considered to be useful in obtaining appropriate housing. Living in rural areas where 'everyone knew everyone' made it difficult for some to obtain housing. The need to address housing, parenting, mental illness and substance abuse as interrelated, rather than as singular issues is highlighted.